ANALYSIS OF P5 IMPLEMENTATION IN ELT FOR JUNIOR HIGH SCHOOL - Aditama, Madya; Tri Asmoro, Heri; Imam Santoso, Yan (Journal of Language Teaching Lingustics and Literature, 2025)
This study investigates the implementation of Projek Penguatan Profil Pelajar Pancasila (P5) in English Language Teaching (ELT) at SMP Muhammadiyah Tersono. The research aims to analyze how English teachers integrate P5 values into language instruction and to identify challenges and pedagogical implications. Using a qualitative descriptive approach, data were collected through interviews, classroom observations, and document analysis involving three English teachers. The data were analyzed thematically following Moustakas’ phenomenological procedures. The findings reveal that P5 values such as collaboration, creativity, and responsibility were effectively embedded through project-based learning activities focusing on local culture, environmental awareness, and entrepreneurship. Teachers applied contextual tasks that connected language learning with real-life situations, enhancing students’ engagement and character formation. However, the study also identified constraints related to limited instructional time, assessment integration, and teachers’ professional readiness. The novelty of this study lies in its exploration of P5-based ELT implementation at the junior high school level, highlighting how national character education can synergize with communicative English teaching. The study contributes to the growing discourse on holistic and value-oriented language pedagogy in Indonesia.